Analisis Teori Fraud Pentagon dalam Mendeteksi Fraud pada Laporan Keuangan Perusahaan yang Terdaftar di Bursa Efek Indonesia - Natalis Christian; Bonadea Visakha (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Abstract The purpose of this study was to analyze the effect of fraud on financial statements using the pentagon theory. The variables that include on fraud pentagon theory are financial stability, external pressure, personal financial needs, financial targets, ineffective monitoring, nature of the industry, BOD turnover, auditor switch, auditor opinion, CEO tenure, and political connections. The dependent variable measured by F-score in this study is corporate fraud. Data were obtained from the annual financial reports for the period 2013 to 2019 as many as 230 companies that met the criteria of 671 companies listed on the Indonesia Stock Exchange. Data tested for 5 years using SPSS version 24 and Eviews with the total research data of 1,150 data minus 231 outliers so that the research sample remained to be 919 data. The results of the study can be inferred that financial stability, personal financial needs have a significant positive effect, while external pressure, ineffective monitoring, auditor switch, CEO Tenure have a significant negative effect on corporate fraud. Variables that have no effect on corporate fraud are financial targets, nature of the industry, BOD turnover, auditor opinion and political connections.